2009
DOI: 10.1111/j.1744-1633.2009.00437.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of age on the outcome of liver surgery. A single institution experience

Abstract: Objective:The aim of the present study was to evaluate the role of age on different types of liver surgery. Methodology: Between 2002 and 2007, 50 patients underwent a variety of liver surgical procedures due to primary or metastatic tumours. Of these, 24 were 70 years old or older, and 26 patients were younger than 70 years old at the time of the operation. Results: Among the patients included in the study, 22 underwent radiofrequency ablation. Another 11 underwent non-anatomical liver resection. The remainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…The combination of cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) plays an important therapeutic role in patients with PC [ 4 ]. On the other hand, elderly patients are traditionally associated more frequently with comorbidities and a reduced capacity to recover or tolerate aggressive surgery [ 5 , 6 ]. Several recent results have shown that age alone does not influence the outcome of surgery and cancer-specific survival in these patients is similar to that of younger patients [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) plays an important therapeutic role in patients with PC [ 4 ]. On the other hand, elderly patients are traditionally associated more frequently with comorbidities and a reduced capacity to recover or tolerate aggressive surgery [ 5 , 6 ]. Several recent results have shown that age alone does not influence the outcome of surgery and cancer-specific survival in these patients is similar to that of younger patients [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Older patients may be discriminated against on the basis of higher risk benefit ratio, protracted recovery to pre‐morbid state and presumed higher morbidity and mortality rates. A number of authors have published the results of hepatic resection in selected older patients with variable age groups . Although most published studies show equivalence in outcomes between older and younger patients, there is a bias towards lower volumes of disease, lesser resections and less preoperative chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…A number of authors have published the results of hepatic resection in selected older patients with variable age groups. [9][10][11][12][13][14][15][16][17] Although most published studies show equivalence in outcomes between older and younger patients, there is a bias towards lower volumes of disease, lesser resections and less preoperative chemotherapy. We have chosen a cut of age of 75 for our cohort of older patients in line with the increased age of the ANBCSP, to assess whether aggressive curative-intent treatment of metastases in these patients is acceptable.…”
Section: Introductionmentioning
confidence: 99%